Navigating Dietary Complexities: Understanding Gluten Intolerance Awareness among Stakeholders ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Eating out is not only a common trend these days but also necessity for many who live away from their  families especially students pursuing higher education. With growing trend of food hypersensitivity catering industry  needs to get driven for such special requirement. Objective: This study aimed to check the awareness of stakeholders  for gluten intolerance with respect to the market and sensory evaluation of the developed alternative. Methodology:  A cross-sectional study was conducted on consumers and food business operators of Central Delhi. Consumers were  18 years and above and claiming to be gluten intolerant. Food business operators were local shopkeepers running  food stalls and bakery. A self -structured questionnaire was designed for stakeholders respectively. Developed gluten  alternative was sensory evaluated by consumers on 9-point hedonic rating scale for its overall acceptability. Data  was analyzed for the stakeholders by using descriptive statistics. Results: The results indicate that majority (53.65%)  consumers were familiar with the symptoms of gluten intolerance like headache and digestive issues. Furthermore,  majority (68.3%) identified rice and corn to be an alternative for gluten. Level of satisfaction from market for availability  of alternatives is medium (61%).Sensory score for developed alternative was 7.19 ±1.53. Regarding food business  operators’ majority (53.12%) receive customer request for availability of gluten free products, 46.87% are affirmative  to provide alternatives subjected to demand of consumers. 53.12% also showcased interest in receiving training or  resources for gluten intolerance and lactose free cooking skills and outsourcing of such food items. Conclusion: In  general stakeholders showcased awareness about their food intolerance and improved availability of alternatives in  market. At the same time willingness of food business operators to offer such products on menu. The study recommends  to provide training to food business operators for provision of diversified menu for prospective consumers.
Keywords: Gluten free; gluten intolerance; food hypersensitivity; stakeholders; food business operators; alternatives; consumer